CFD optimization optimization of low head turbines using Fisher-Franke guidelines - Angulo, Mauricio Abel (2013)
Poor design of low head turbine intakes can lead to a non-uniform flow incoming to the machine inlet. This can affect performance and operational features along its useful life. In most of the cases, turbine acceptance test are performed with ideal intake conditions without considering the actual upstream flow condition. This situation may result in different behavior between the model and the prototype, so it is advisable to model the flow approaching the inlet section. Such modeling is usually studied by physical modeling which can be costly and may require excessive construction and test time, especially when an optimized design is required, due to this fact is preferred CFD modeling. This work aims to propose the use of a methodology that allows the optimization of low head turbine intakes. The methodology takes as its starting point the Fisher-Franke´s authors guidelines. In particular this paper shows the design optimization of a bulb intake, where the flow pattern upstream the inlet section it is not usual, so the main concern was to guarantee a high quality flow at the turbine inlet section.